Біологічні особливості сортів Clematis L. з колекції Національного ботанічного саду ім. М.М. Гришка НАН України - Tsysaruk, T.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
In article data on phenological supervision, and also a method of reproduction of variety of Clematis L. in M.M. Gryshko National Botanical Gardens of the NAS of Ukraine are given.